2010
DOI: 10.1007/s11426-010-4051-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism study and molecular design in controlled/“living” radical polymerization

Abstract: This tutorial review summarizes recent progress in the research field of controlled/"living" radical polymerization (CLRP) from Soochow University. The present paper gives a broad overview of the mechanism study and molecular design in CLRP. The mechanism study in CLRP aided by microwave, initiated by -radiation at low temperature, mediated by iron, in reversible addition-fragmentation chain transfer (RAFT) polymerization and the mechanism transfer between different CLRP processes are reviewed and summarized.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 159 publications
0
4
0
Order By: Relevance
“…Microwave-Assisted RAFT Polymerization Three reviews on microwave-assisted polymerization [65,98,99] and two reviews specifically on microwave-assisted RAFT polymerization [30,31] have appeared. The number of papers on …”
Section: Atrp-initiated Raft Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave-Assisted RAFT Polymerization Three reviews on microwave-assisted polymerization [65,98,99] and two reviews specifically on microwave-assisted RAFT polymerization [30,31] have appeared. The number of papers on …”
Section: Atrp-initiated Raft Polymerizationmentioning
confidence: 99%
“…[62] The process is also given substantial coverage in most recent reviews that, in part, relate to polymer synthesis, living or controlled polymerization or novel architectures. Some of those that include significant mention of RAFT polymerization include reviews on RDRP, [63] mechanism and reagent design, [11,64,65] click chemistry, [66][67][68][69][70][71][72] synthesis of telechelics, [73] the polymerization of carbazole-containing monomers, [74] N-vinyl-1,2,3-triazoles, [75] N-vinyl heterocycles, [76] fluoro-monomers, [77] and glycomonomers, [78][79][80] synthesis of metallopolymers, [81] conjugated block copolymers, [82] dye-functionalized polymers, [83] stimuliresponsive polymers, [84,85] complex architectures, [86,87] polyolefin blocks, [88] biopolymer-polymer conjugates and bioapplications, [59,[89][90][91][92][93] polysaccharide modification, [94,95] polymerization in heterogeneous media, [96,97] microwave-assisted polymerization, [65,98,99] industrial prospects for RDRP, [100,…”
Section: Introductionmentioning
confidence: 99%
“…The controlled/living radical polymerization (C/LRP) has attracted many attention due to its various promising potential applications for the tailor-made polymer architectures since the 1990s [1] . One of the driving forces behind the recent interest in control living free-radical procedures, such as nitroxide-mediated polymerization (NMP) [2] , atom transfer radical polymerization (ATRP) [3] , and reversible addition-fragmentation chain transfer (RAFT) [4] polymerization, has been demonstrated that these novel techniques provide an unprecedented opportunity for designing and controlling macromolecular architectures under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al summarized their achievements in controlled radical polymerizations [16], which is fundamental to develop new radical polymerization techniques, and an abundance of polymer materials with different topologies have been prepared through this technique. They specially focused on the molecule design and mechanism study in CRP, and the CRP initiated at different conditions.…”
mentioning
confidence: 99%